Beyond pollination: diversity of secretory structures during flower development in different legume lineages - Barros,Thais Cury De (2017)
ABSTRACT Floral secretory structures are usually associated with the attraction of pollinators, but may also play an important role in the mechanisms of plant protection. This study aimed to show the diversity of secretory structures present in the developing flowers of 15 legume species belonging to different clades and to associate them with functions other than the pollinator attraction. Buds, flowers and developing axis of inflorescence were processed for surface, histological, and ultrastructural analyses. The species investigated displayed a wide diversity of secretory structures in developing flowers such as phenolic cells and/or tissues, mucilaginous cells, secretory cavities, secretory trichomes and colleters. Each type of secretory structure exhibited variation in morphology and location in the flower and/or axis of inflorescence depending on the species. Special mucilage cells, secretory cavities, secretory trichomes and colleters have great potential for comparative morphological studies due to their diversity of forms or restricted occurrence to certain taxa, contributing to a more robust morphological data base for the new clades emerging in Leguminosae. The scarcity of reports about floral secretory structures of Leguminosae seems to be more related to deficient sampling than to the absence of such structures in the group, which highlights the need for further investigation.